Production performance and biochemical profile of sea lettuce (Ulva lactuca): Influence of site-specific ecological factors and cultivation strategies - Chamily, Farjana; Mohiuddin, Md; Mostakim, Mohammad; Rahman, Md; Souhardya, Sazeed; Nahiduzzaman, Md; Khan, Md Sadequr; Asaduzzaman, Md. (Elsevier, 2025)
Production performance and biochemical characteristics of seaweed under varying cultivation strategies and ecological conditions provide crucial insights for improving sustainable farming practices. Therefore, this study aims to investigate the production performance and biochemical profile of sea lettuce (Ulva lactuca) under three farming systems, namely floating long-line (FLL), off-bottom long-line (OBLL), and off-bottom net (OBN), and three site-specific (Khurushkul, Nuniachora, and Sonapara) ecological conditions for a period of nine months (October 2022 to June 2023). Depending on the site suitability for different cultivation systems, 15 plots (5 FLL, 5 OBLL, and 5 OBN) were established in Nuniachora, 10 plots (5 FLL, 5 OBLL) were established in Sonapara, and 5 plots (FLL) were established in Khurushkul of the Cox’s Bazar district, Bangladesh. Depending on the cultivation months, we partially harvested U. lactuca every 15–30 days once it reached 25–35 cm in length. Results showed that the gross weight biomass (GWB) of U. lactuca cultured in the FLL (F = 200.43, p < 0.001) cultivation system was 45.38% and 39.85% higher compared to OBN and OBLL, respectively. The average daily growth rate (DGR) was found to be 11%–13% higher in the FLL method (F = 236.11, p < 0.001). Location-based comparisons indicated a significantly higher (p < 0.05) U. lactuca production in Khurushkul, followed by the Nuniarchora, and the lowest was observed in Sonapara. Seasonality influenced the production performances of U. lactuca, with significantly higher (p < 0.05) growth observed from December to March due to favourable physio-chemical parameters. Multivariate analysis revealed that high salinity, pH, and nutrient concentrations positively influenced growth performances, while high temperature, turbidity, and total suspended solids (TSS) had negative effects. U. lactuca harvested from the FLL and OBN systems contained 14.3% and 9.44% higher amounts of protein (F = 36.77, p < 0.001) than the OBN system. The fatty acid analysis showed that U. lactuca from the FLL and OBN systems contained a significantly lower amount of saturated fatty acids but a higher amount of monounsaturated and n-6 polyunsaturated fatty acids compared to the OBLL system. Among the heavy metals and minerals analyzed, U. lactuca harvested from the FLL system contained significantly (p < 0.05) higher amounts of Na and K and lower amounts of Pb, Cr, Co, and Fe. The findings of the present study underscore the superiority of the floating long-line cultivation system for U. lactuca, highlighting its potential for sustainable farming practices to address global food security and utilization in various industrial applications.